Pengaruh Number Sense dan Working Memory terhadap Berpikir Kreatif Calon Guru Matematika Saat Problem Posing - Muhammad Rizaldi; Oktaviana Ainun Ratnawati; Putri Sasalia (Program Studi Pendidikan Matematika, FKIP Universitas Muslim Maros, 2025)
Mathematical creative thinking is an essential skill that needs to be developed in pre-service mathematics teachers. This skill is needed for them to be able to compose or propose problems that make students think creatively as well. The purpose of this study was to investigate the impact of number sense and working memory on creative thinking of pre-service mathematics teachers when conducting problem posing activities. This research was a quantitative research through ex post facto approach. The subjects in the study were 121 Mathematics Education students at one of the Central Kalimantan Universities. This study used ordinal logistic regression data analysis techniques. The results of this study showed that the average number sense and working memory were 27.17 and 46.26 out of 100, respectively. Descriptively, the average number sense and working memory of students were very low which was far below the maximum range. Furthermore, there were 4 people in the very creative category, 10 people in the creative category, 62 people in the less creative category, and 45 people in the uncreative category. The majority of prospective teachers were in the less creative category, indicating their low creative thinking ability descriptively. Furthermore, number sense had a significant effect on the creative thinking of pre-service mathematics teachers in problem posing activities, while working memory did not show a significant effect.